The Laboratory Cockroach - Bell, W. J. author. aut Link
IX, 161 p. 127 illus.
Keywords: Cockroaches are ideal subjects for laboratory investigation at all educational levels. Compared with many other laboratory animals, cockroaches are easily and inexpensively maintained and cultured and require relatively little space. They are hardy and are readily available. The purpose of this book is to provide background material and experimental leads for utilizing cockroaches in the teaching laboratory and in designing research projects. The level of difficulty of the experiments varies according to the depth of understanding desi red by the instructor. In most cases at least a part of each experiment or technique can be incorporated into the laboratory component of elementary, high school or college curriculum. Sections of the lab book are appropriate for courses in Animal Behavior, Entomology, Organismic Biology and Insect Physiology. Aside from this main purpose, the book also provides a wealth of experimental ideas and techniques for a scientist at any level of education. Lawrence, Kansas June 15, 1981 W. J. B. ACKNOWLEDGEMENTS. Virtually all graduate students who have worked on cockroach research in my laboratory have knowingly or unknowingly contributed to this book. The most important contribution was from Sandy Jones McPeak, who encouraged me to finish the project. Segments of various chapters were conceived, developed or reviewed by Michael D. Breed, Sandy Jones McPeak, Michael K. Rust, Coby Schal, Thomas R. Tobin, W. Alexander Hawkins, Gary R. Sams and Chris Parsons Sams.